Functionality of strategic supplier relationships - A comparative case study - Kohtala , Kristiina (My University, 2010)
The present study aims at analyzing client company’s strategic supplier relationships. The study’s objective is to evaluate the studied supplier relationships’ functionality and based on this evaluation to make concrete proposals of improvement. The conceptual platform of the thesis builds on the concepts of networking, different levels of supplier relationships and their special characteristics. Special attention is given to strategic supplier relationships. Underlying networking theories are also discussed. Finnish and foreign literature and empirical studies on industrial buyer-supplier relationships were used as a basis for closer analysis. The conceptual framework builds on previous literature and theoretical models which helped to create as wide and thorough viewpoint as possible from the most important key elements affecting buyer-supplier relationships' functionality. The empirical research was conducted as a comparative case study. The client company and six of its strategic suppliers were interviewed by using semi-structured interviews. Themes for the interviews were based on previous theory and the conceptual framework created. The empirical results gave important information about the current state of all studied supplier relationships. Similarities and differences between the studied cases were also evaluated. Relationships were examined by using a dyadic approach, which means that studied relationships and their key elements were evaluated from both  the buyer’s and supplier’s perspective. The results revealed that functionality of the studied six supplier relationships is mainly built on fluency of daily purchasing routines, social interaction, suppliers’ flexibility and willingness to service as well as people’s professional skills and work experience in companies’ interfaces. There are also development needs in certain areas of the relationships in all studied cases. In particular, the technical organisation of the cooperation including joint structures and processes needs a clearer and more systematic approach in all interviewed companies. The development of cooperation towards a more strategic level also requires developing in all the cases studied.
Keywords: Dyad; networking; partnership; strategic supplier; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|